The role of coronavirus infection Covid -19 in causing liver damage - Numonova D.G.; Saliev D.K. (Zien Journals, 2022)
Post covid syndrome can develop in all patients who have had COVID-19, regardless of the severity of the disease. The clinical picture of post covid syndrome is very diverse, but the most common are asthenic disorders, anxiety-depressive disorders (TDD) and cognitive impairment (CN).
Keywords: COVID-19; post covid syndrome; cognitive impairment; depression; SARS-CoV-2, indicators